STRATEGIES D’ADAPTATION DES ELEVEURS CAPRINS EN ZONE MONTAGNEUSE DE TIZIOUZOU (ALGERIE) - Azeddine, Mouhous; Ammar, Kadi Si; Fatima, Brabez (European Scientific Journal, ESJ, 2015)
Public policy incentive in Algeria milk production have targeted dairy goat farms in order to increase production. To capture these incentives, farmers adapt to different strategies depending on their staffing means of production. To understand the diversity of these strategies, monitoring of 16 goat farms is made from March 2012 to February 2013 in the mountainous region of Tizi-Ouzou. Three coping strategies are identified: (i) large farms of type "milk" that produce only milk; (ii) the average farms of "mixed" type that produce milk and meat; (iii) small farms type "meat" dominant meat. Goats receive concentrate feed throughout the year, 180 g / goat / day in type milk and 150 g / goat / day in mixed and meat type. Pastures are used 6h / day throughout the year and for all farms. The average daily milk production does not exceed 1.3 kg / goat. However, in the milk type, it reaches 2 kg / goat milking / day. The annual sale of goat milk is approximately 622 kg for milk type, but 218 and 266 kg respectively for the meat and mixed type. The milk type generates an income of more than 2.7 million DA / year. Incomes of mixed meat types are 440 000 and 222 600 DA / year. The study shows that the level of financial allocation is the lever that dictates the choice of production strategies.